Preparation of mesoporous silica/sodium alginate composites and its removal performance of radioactive Sr2+ - JIANG Wei; CAI Xiaodie; WEN Xinyu; CHEN Sili; WANG Jinsong; ZHANG Zhengke (Gongye shui chuli)
The extensive use of nuclear energy has brought new challenges to nuclear wastewater treatment, and it is urgent to develop absorptive materials with promising applications. The mesoporous silica(HMSS, MCM-41, SBA-15)/sodium alginate(SA) composites were constructed by embedding method, and the effects of raw material ratio, pH, adsorption time, initial concentration, adsorbent dosage, and competing ions on the Sr2+ adsorption performance of composite materials were explored. The composite materials before and after adsorption were characterized by fourier transform spectroscopy(FT-IR), scanning electron microscopy(SEM) and energy dispersive spectroscopy(EDS). The results showed that under the conditions of T=298 K, pH=7.0, t=240 min, the saturated adsorption capacities of HMSS/SA(1∶3), MCM-41/SA(1∶3) and SBA-15/SA(1∶3) for Sr2+ could reach 49.67, 40.54 mg/g and 34.90 mg/g, respectively. The adsorption process was consistent with the Langmuir isotherm model and the pseudo-second-order reaction kinetics model, indicating that chemical adsorption characterized by monolayer adsorption was primarily involved. In the presence of competing ions Na+, K+, Ca2+ and Mg2+, the inhibitory strength followed Na+≈K+<Mg2+<Ca2+, and still a high selectivity for Sr2+ in Cs+ and Sr2+ systems. In addition, HMSS/SA(1∶3), MCM-41/SA(1∶3) and SBA-15/SA(1∶3) had good recycling performance.